Collaborative forward‐looking imaging and reconnaissance technology for manned/unmanned aerial vehicles. Issue 19 (9th August 2019) - Meng, Ziqiang; Li, Xiaoming; Lu, Chengjun; Zhu, Daiyin
Abstract : With the imaging advantage of bistatic forward‐looking synthetic aperture radar, collaborative forward‐looking imaging and reconnaissance technology for manned/unmanned aerial vehicles could be performed, in which unmanned aerial vehicle can realise two‐dimensional (2‐D) and high‐resolution imaging and further attacking targets in its straight‐ahead position. However, there exists more complicated space‐variance property in this special configuration than traditional mono‐static SAR. Such property will lead to performance deterioration of imaging if not corrected effectively. To address this problem, 2‐D frequency spectrum with high precision is first obtained based on squint minimisation method here, and then a novel‐phase space‐variance correction method is developed through polynomial fitting. Imaging focus performance on targets could be improved significantly with authors' method. Several simulations for scattering targets confirm its validity.